Thermal stability enhancement of guar‐based hydraulic fracturing fluids by phosphate treatment. Issue 9 (4th October 2018) - Ma, X.; Wang, H.; Boyd, W. W.; Cheng, M.; Yao, C.; Lei, G.
ABSTRACT: Guar gum (GG), along with its derivatives [e.g., hydroxypropyl guar (HPG)], is an important thickening agent in the hydraulic fracturing fluid system. However, as the oil reservoir gets deeper, GG is unable to tolerate the elevated temperature. In this study, the thermal stability of GG and HPG can be increased up to 95% and 80%, respectively, when phosphates are used as thermal stabilizer. The thermal stability is highest when the usage of phosphate is 1.84 mmol L −1 KH2 PO4 for GG and 2.27 mmol L −1 K2 HPO4 for HPG and the pH is 6.25–6.90 for GG and 6.25–8.75 for HPG. Furthermore, the heated GG with phosphate treatment demonstrates excellent crosslinking ability, which suggests that phosphate can be a good alternative for current thermal stabilizers and has potential application in the high‐temperature formation oil or gas production. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47119. Abstract : The thermal stability enhancement of guar‐based fracturing fluids using phosphates